Effect of temperature on the growth of boron nitride interfacial coatings on SiC fibers by chemical vapor infiltration. Issue 15 (15th October 2019) - Dai, Jianwei; Wang, Yiguang; Xu, Zhenhua; Mu, Rende; He, Limin
Abstract: In order to improve bonding property between SiC fibers and matrix of SiCf /SiC composites, boron nitride (BN) interfacial coatings were synthesized by chemical vapor infiltration. BN coatings were fabricated from BCl3 –NH3 gaseous mixtures at four different temperatures (843 °C, 900 °C, 950 °C and 1050 °C) with different deposition times. Growth kinetics, nucleation and growth processes, microstructure and chemical composition of boron nitride coatings were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Raman spectrometry. Results showed that deposition rate increased as the temperature increased from 843 °C to 950 °C. However, deposition rate decreased slightly from 23.10 ± 0.85 nm/min (950 °C) to 21.39 ± 0.67 nm/min when the temperature was increased further to 1050 °C. It could be due to the nucleation occurring in the gas and the consumption of a large amount of BCl3 and NH3 . When deposition temperature was 843 °C, BN grains deposited on top layer of the coating could not completely cross Ehrlich-Schwoebel barrier and grew in island growth mode. On the other hand, the deposition pattern followed a layer-by-layer growth mode when deposition temperature was 1050 °C. Deposition temperature significantly affected the microstructure of as-deposited BN coatings. At 843 °C, 950 °C and 1050 °C, the coatings presented amorphous, polycrystalline and hexagonal structures, respectively.